The cortisol awakening response predicts same morning executive function: results from a 50-day case study. (2nd November 2015) - Law, Robin; Evans, Phil; Thorn, Lisa; Hucklebridge, Frank; Clow, Angela
Abstract: A relationship between individual differences in trait estimates of the cortisol-awakening response (CAR) and indices of executive function (EF) has been reported. However, it is difficult to determine causality from such studies. The aim of the present study was to capitalise upon state variation in both variables to seek stronger support for causality by examining daily co-variation. A 50 days researcher–participant case study was employed, ensuring careful adherence to the sampling protocol. A 24-year-old healthy male collected saliva samples and completed an attention-switching index of EF on the morning of each study day. Subsidiary control measures included wake time, sleep duration, morning fatigue, and amount of prior day exercise and alcohol consumption. As the CAR preceded daily measurement of EF, we hypothesised that, over time, a greater than average CAR would predict better than average EF. This was confirmed by mixed regression modelling of variation in cortisol concentrations, which indicated that the greater the increase in cortisol concentrations from 0 to 30 min post-awakening (CAR) the better was subsequent EF performance at 45 min post-awakening ( t = 2.29, p = 0.024). This effect was independent of all potential confounding measures. Results are discussed in terms of implications for the understanding of the relationship between the CAR and the cognitive function, and the previously suggested role of the CAR in "boosting" an individual's performance for the day ahead.